Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The effectiveness of a proposed study unit in economic geography subject in developing knowledge, skills and attitudes of Omani female students at grade eleven towards entrepreneurship in Muscat Governorate in the Sultanate of Oman Mrs. Najah Salim Hudeb Al-Habsi 2. Extent does the primary school mathematics teachers in Makkah Al-Mukarramah aware of the manifestations of difficulties in learning arithmetic (dyscalculia) among female students Mrs. Sawsan Ahmed Al-Afifi 3. The Effect of a Program based on Gardner’s Five Minds Theory on the Development of Undergraduate Mathematics Graduate Students’ Creative Thinking at the Faculty of Education- Sana’a University Mrs. Eman Ahmed Al-Maqtari , Prof. Radman Mohamad Saeed 4. The Hidden Curriculum and its Role in Students’ Acquisition of Cultural Values and Behavioral Patterns Dr. Hani Ahmad Alkriameen, Dr. Ahmed Odeh Qarareh 5. The Status of Using Blended Learning in Teaching the English Language at High Schools from the Teachers’ Point of View Dr. Amal Mohammad Al-Momani 6. The effectiveness of employing 3D interchange graphics in a diffuse learning environment on the science skills of health and life path students in the secondary stage Co-Prof. Khaled Nasser Alqahtani 7. The impact of blended learning on students’ motivation towards learning and social studies teachers’ attitudes towards it in Al-Sharqiyah South Governorate in the Sultanate of Oman Mrs. Aisha Abdullah Muhammad Al Majali, Mr. Fahd Salem Saif Al-Masrouri 8. Improving English Speaking Skills at Saba University Dr. Khaled Mohsen Mohamed Zuheer